Fear Of Missing Out sebagai Prediktor Psychological Well-Being pada Mahasiswa Pengguna Instagram - Irena Syva Salbilah Ulfa; Ika Andrini Farida (Flourishing Journal, 2023)
Many young adults have low Psychological Well-Being, and one of the causes is Fear of Missing Out. Someone who is Fear of Missing Out will be very interested in participating in social media, such as Instagram. This research aims to test the hypothesis that there is a predictive relationship between Fear of Missing Out and Psychological Well-Being in students at the Faculty of Psychology, State University of Malang who actively use Instagram. Correlational research is the method used in this research. The data analysis technique in this research uses simple linear regression. The purposive sampling technique was chosen to collect data for this research and obtained 187 subjects with the criteria of actively using Instagram. The instruments used were the Fear of Missing Out scale and the Psychological Well-Being scale. The results of this study show that the hypothesis is proven, namely Fear of Missing Out can predict Psychological Well-Being with a value of R2 = 0.099. This can be interpreted that FoMO as a predictor has an effective contribution of 9.9% to the Psychological Well-Being of students at the Faculty of Psychology, the State University of Malang who use Instagram. AbstrakBanyak individu, khususnya usia dewasa awal yang memiiki Psychological well-being (PWB) rendah, salah satu penyebabnya adalah Fear of Missing Out (FoMO). Seseorang yang FoMO akan sangat tertarik untuk berpartisipasi di media sosial, seperti instagram. Penelitian ini memiliki tujuan untuk menguji hipotesis bahwa ada hubungan prediktif antara FoMO dan psychological well-being (PWB) pada mahasiswa Fakultas Psikologi Universitas Negeri Malang yang aktif menggunakan instagram. Metode kuantitatif dengan jenis penelitian korelasional adalah metode yang digunakan dalam riset ini. Teknik analisis data dalam riset ini menggunakan regresi linear sederhana. Populasi pada penelitian ini adalah mahasiswa aktif S1 Fakultas Psikologi Universitas Negeri Malang, laki-laki dan perempuan, dan berusia 18-25 tahun. Teknik purposive sampling dipilih dalam pengumpulan data penelitian ini dan mendapatkan subjek berjumlah 187 orang dengan kriteria aktif menggunakan instagram. Instrumen yang digunakan yaitu skala Fear of Missing Out dan skala Psychological Well-Being. Hasil penelitian ini menunjukkan bahwa hipotesis terbukti, yaitu FoMO dapat memprediksi PWB dengan nilai R2 = 0,099. Hal ini dapat diartikan bahwa FoMO sebagai prediktor memiliki kontribusi efektif sebesar 9,9% terhadap PWB mahasiswa Fakultas Psikologi Universitas Negeri Malang pengguna instagram.